CFD modeling and analysis of the behavior of 30° and 45° inclined dense jets – new numerical insights. Issue 2 (2nd July 2016) - Kheirkhah Gildeh, Hossein; Mohammadian, Abdolmajid; Nistor, Ioan; Qiblawey, Hazim; Yan, Xiaohui
Abstract : A three-dimensional numerical model of inclined turbulent jets with negatively buoyant discharge into stationary ambient water is presented in this paper to study certain jet parameters with turbulence schemes that have not been employed before in this context such as standard Boussinesq gradient diffusion hypothesis and general gradient diffusion hypothesis to account for the buoyancy-induced turbulence generation. Two jet discharge angles have been chosen for this study: 30° and 45° with the horizontal. These two angles are chosen in this study due to lower terminal rise heights for 30° and 45°, a fact which is critically important for discharges of effluent into shallow waters compared to higher angles than these values. The spatio-temporal jet evolutions for these cases have been modeled using OpenFOAM open-source CFD code, which is based on Finite-Volume Method. Results presented in this paper deal with the geometrical and flow properties of the inclined dense jets. The densimetric Froude number of the effluent at the nozzle ranges between 10 and 34. Two Reynolds-Averaged Navier–Stokes turbulence models are applied to evaluate the accuracy of the numerical predictions: the realizable k – ε (a two-equation model) and the Launder Reece Rodi (a Reynolds Stress Model – RSM).